2016
DOI: 10.2174/1573403x12666160301120030
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Comprehensive Approach to Management of Acute Decompensated Heart Failure

Abstract: Heart failure (HF) has a high incidence and prevalence in the USA and worldwide. It is a very common cause of significant morbidity and mortality with serious cost implications on the US health sector. The primary focus of this review is to synthesize an effective comprehensive care plan for patients in acute decompensated heart failure (ADHF) based on the most current evidence available. It begins with a brief overview of the pathophysiology, clinical presentation and evaluation of patients in ADHF. It then r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is possible that the discomfort associated with increased diuresis causes patients to take lower or irregular doses and, as a secondary consequence, to intentionally miss their follow-up appointments. This results in non-optimal compensation of high volemia, increased risk of cardiovascular decompensation, and poorer prognosis, which in turn necessitates a higher dosage of diuretics due to disease exacerbation and increased fluid retention, producing a vicious cycle [25]. In the present study, treatment with beta-blockers and ACE inhibitors or ARBs correlated positively with pharmaceutical compliance and regular follow-up appointment-keeping, but a negatively one on the overall compliance level and healthy lifestyle.…”
Section: Plos Onementioning
confidence: 58%
“…It is possible that the discomfort associated with increased diuresis causes patients to take lower or irregular doses and, as a secondary consequence, to intentionally miss their follow-up appointments. This results in non-optimal compensation of high volemia, increased risk of cardiovascular decompensation, and poorer prognosis, which in turn necessitates a higher dosage of diuretics due to disease exacerbation and increased fluid retention, producing a vicious cycle [25]. In the present study, treatment with beta-blockers and ACE inhibitors or ARBs correlated positively with pharmaceutical compliance and regular follow-up appointment-keeping, but a negatively one on the overall compliance level and healthy lifestyle.…”
Section: Plos Onementioning
confidence: 58%
“…23 It is well established that the frequency and duration of heart failure-related hospitalizations are the major contributors to the huge annual economic burden of heart failure. [24][25][26][27] Although current evidence shows that BBT decreases heart failure-related readmissions in patients with HFrEF, 24,28 we are not aware of any report in the literature with similar finding among patients with HFrEF concurrently using cocaine. In their study, Nguyen et al reported no significant differences in heart failure readmissions, death, major adverse cardiovascular events (MACE), or all composite end points in patients having heart failure with cocaine use versus patients having heart failure without cocaine use when treated with a b-blocker.…”
Section: Principal Findingsmentioning
confidence: 79%